2014
DOI: 10.1093/jac/dku271
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals clonal expansion of multiresistant Staphylococcus haemolyticus in European hospitals

Abstract: ObjectivesStaphylococcus haemolyticus is an emerging cause of nosocomial infections, primarily affecting immunocompromised patients. A comparative genomic analysis was performed on clinical S. haemolyticus isolates to investigate their genetic relationship and explore the coding sequences with respect to antimicrobial resistance determinants and putative hospital adaptation.MethodsWhole-genome sequencing was performed on 134 isolates of S. haemolyticus from geographically diverse origins (Belgium, 2; Germany, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 52 publications
5
73
1
1
Order By: Relevance
“…S. aureus versus Staphylococcus epidermidis and Staphylococcus haemolyticus shows *75% average nucleotide identity values, which proves their close genetic relatedness (Konstantinidis et al, 2006;Lamers et al, 2012). That fact is also indicated in the topology of a dendrogram based on the 16S rRNA sequence in Bergey's Manual of Systematic Bacteriology (Vos et al, 2009) as well as in whole-genome sequencing projects comparing different staphylococci strains (Takeuchi et al, 2005) and 134 isolates of S. haemolyticus from geographically diverse origins (Cavanagh et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…S. aureus versus Staphylococcus epidermidis and Staphylococcus haemolyticus shows *75% average nucleotide identity values, which proves their close genetic relatedness (Konstantinidis et al, 2006;Lamers et al, 2012). That fact is also indicated in the topology of a dendrogram based on the 16S rRNA sequence in Bergey's Manual of Systematic Bacteriology (Vos et al, 2009) as well as in whole-genome sequencing projects comparing different staphylococci strains (Takeuchi et al, 2005) and 134 isolates of S. haemolyticus from geographically diverse origins (Cavanagh et al, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…During the next decades, multiresistance of S. haemolyticus was reported with an increasing frequency. Most of the analysed strains were resistant to the commonly used antiseptic agents and antibiotics, notably more frequently than strains of any other species amongst CNS (Cavanagh et al, 2014;Hope et al, 2008). Many authors reported S. haemolyticus strains as resistant to one or more antibiotics amongst penicillins, cephalosporins, macrolides, tetracyclines, quinolones, aminoglycosides, glycopeptides and fosfomycines (Holden et al, 2013;Lebeaux et al, 2012;Shittu et al, 2004).…”
Section: Multiresistancementioning
confidence: 99%
See 3 more Smart Citations